Trace amine receptor (version 2019.4) in the IUPHAR/BPS Guide to Pharmacology Database (IUPHAR/BPS Guide to Pharmacology CITE, 2019)
Trace amine-associated receptors were discovered from a search for novel 5-HT receptors [9], where 15 mammalian orthologues were identified and divided into two families. The TA1 receptor (nomenclature as agreed by the NC-IUPHAR Subcommittee for the Trace amine receptor [53]) has affinity for the endogenous trace amines tyramine, β-phenylethylamine and octopamine in addition to the classical amine dopamine [9]. Emerging evidence suggests that TA1 is a modulator of monoaminergic activity in the brain [90] with TA1 and dopamine D2 receptors shown to form constitutive heterodimers when co-expressed [28]. In addition to trace amines, receptors can be activated by amphetamine-like psychostimulants, and endogenous thyronamines.